Magnetic metal particle and waste fabric derived carbon composite wave-absorbing material and preparation method thereof

Through hydrothermal method and high-temperature heat treatment process, a composite carbon absorbing material derived from cobalt nickel metal particles and waste tissue paper was prepared, solving the problems of complex process, high cost and uneven composition in the existing technology, and achieving efficient electromagnetic wave absorption performance and low-cost preparation of absorbing materials.

CN119767656APending Publication Date: 2025-04-04YANTAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891476.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing magnetic metal and carbon fiber composite wave absorbing materials have complex processes, high costs, uneven composition and poor morphological regulation, making it difficult to meet the needs of efficient electromagnetic wave absorption.

Method used

By using hydrothermal method and high-temperature heat treatment process, lightweight and high-performance cobalt-nickel metal particles and waste tissue tissue derived carbon composite wave absorbing materials are prepared by using waste tissue tissue fiber as the substrate.

Benefits of technology

The lightweight and high-performance cobalt-nickel metal particles and waste tissue-derived carbon composite absorbing materials have been achieved. It has excellent electromagnetic wave absorption performance, the maximum reflection loss reaches -40.22dB, the effective absorption bandwidth is 4.5GHz, and the cost is low, the composition is uniform, and the morphology is adjustable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767656A_ABST
    Figure CN119767656A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electromagnetic wave absorbing materials, and discloses a magnetic metal particle and waste fabric derived carbon composite wave absorbing material which is composed of micron-sized carbon fibers and metal particles embedded in the surfaces of the micron-sized carbon fibers. The carbon fiber is formed by carbonizing and deriving waste facial tissues, and the transverse size is 5-6 [mu] m; magnetic metal particles are inlaid on the surface of the fiber, the particle size is about 0.47 mu m, recycling of waste fabric is achieved, the process is simple and convenient, process parameters are adjustable, the prepared CoNi and carbon wave-absorbing material shows a matched electromagnetic parameter level, good wave-absorbing performance is achieved under the synergistic effect of polarization, electric conduction loss, magnetic resonance and other mechanisms, and the wave-absorbing material is suitable for being used in the field of wave-absorbing materials. When the packing ratio is 30wt% and the matching thickness is 1.3 mm, the minimum reflection loss and the effective absorption bandwidth respectively reach-40.22 dB and 4.5 GHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electromagnetic wave absorbing materials, in particular to a composite absorbing material of magnetic metal particles and waste fabric-derived carbon and a preparation method thereof. Background Art

[0002] With the continuous increase in per capita fiber consumption, my country produces a large amount of waste textiles every year. The development of efficient waste fabric recycling and reuse technology can not only save resources and reduce the burden of waste on the environment, but also create new economic value. At the same time, with the rapid development of electronic equipment and wireless communication technology, the problem of electromagnetic pollution has become increasingly prominent. The demand for absorbing materials in modern society has increased rapidly, especially in the fields of military, communications, electronic equipment, etc., the application of absorbing materials is particularly important.

[0003] In this context, research and development of new technologies that combine the recycling of waste fabrics with the preparation of absorbing materials has important practical significance and broad application prospects. Waste fabrics contain a wealth of fiber materials, which have good physical and chemical properties. Through reasonable modification and treatment, they can be given excellent electromagnetic wave absorption performance.

[0004] Current research shows that Wang et al. (C. Wang, H. Jiang, B. Cui, X. Xu, Y. Wang, C. Wang, ZIF-67 derived Co@carbon nanotubes anchored on carbon fiber for efficient microwave absorption and mechanical enhancement, Ceram. Int. 50 (2024) 1147-1158.) constructed a three-dimensional heterostructured Co@carbon nanotube / carbon fiber composite material. By optimizing the component content, introducing rich heterogeneous interfaces and appropriate defect concentrations, an effective absorption bandwidth of 4 GHz and a reflection loss of -45.11 dB were obtained at a thickness of 1.15 mm. Wei et al. (Y. Wei, H. Liu, S. Liu, M. Zhang, Y. Shi, J. Zhang, L. Zhang, C. Gong, Waste cotton-derived magnetic porous carbon for high-efficiency microwave absorption, Compos. Commun. 9 (2018) 70-75.) prepared nickel nanoparticles / cotton-derived carbon composites by in-situ growth strategy. Under the condition of low filler loading and matching thickness, it showed broadband absorption characteristics; Jin et al. (H. Jin, H.-M. Wen, Q. Hong, J. Lin, J. Li, J. Hu, NiCo@NPC@CF nanocomposites derived from NiCo-MOF / cotton for high-performance electromagnetic wave absorption, J. Mater. Chem. C. 10 (2022) 8310-8320.) also selected cotton-derived carbon and composited it with cobalt nickel nanoparticles, and obtained excellent wave absorption performance by regulating the heat treatment temperature.

[0005] Although certain progress has been made in the research on magnetic metal and carbon fiber composite absorbing materials, the existing technology has problems such as complex process, high cost, uneven composition, poor morphology controllability, etc. Therefore, the present application proposes a magnetic metal particle and waste fabric derived carbon composite absorbing material and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide a composite absorbing material of magnetic metal particles and waste fabric-derived carbon and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a magnetic metal particle and waste fabric-derived carbon composite absorbing material, the material is composed of micron-sized carbon fiber and magnetic metal particles embedded on the surface of the micron-sized carbon fiber, and the material is applied to the field of absorbing materials. When the matching thickness is 1.3 mm, the minimum reflection loss reaches -40.22 dB, and the effective absorption bandwidth is 4.5 GHz.

[0008] Preferably, the micron-sized carbon fiber is tissue-derived carbon fiber, and has a lateral dimension of 5-6 μm.

[0009] Preferably, the average particle size of the magnetic metal particles is about 0.47 μm.

[0010] According to the above-mentioned method for preparing a composite wave absorbing material derived from magnetic metal particles and waste fabrics, the method comprises the following steps:

[0011] Step S1, soaking the waste fabric in anhydrous ethanol, filtering and washing, drying, and cutting into sheets of 10*10 cm2 for standby use.

[0012] Step S2, dissolving the soluble metal salt and urea in deionized water, performing magnetic stirring, controlling the stirring time, obtaining a uniform solution, pouring the obtained solution into a polytetrafluoroethylene liner, placing the treated sheet-like waste fabric therein, performing hydrothermal treatment, controlling the hydrothermal time and temperature, filtering, washing and drying after the hydrothermal treatment, and obtaining a composite precursor of basic carbonate and waste fabric;

[0013] Step S3, heat-treating the basic carbonate and waste fabric composite precursor obtained in step S2 under an inert atmosphere to obtain magnetic metal particles and waste fabric-derived carbon composite materials.

[0014] Preferably, the waste fabrics in step S1 include daily-use cotton facial tissues and other waste cotton products.

[0015] Preferably, the soluble metal salt in step S2 is one or more combinations of other acid metal salts such as cobalt nitrate, nickel nitrate, cobalt chloride, nickel acetate, and iron nitrate, and the ratio between the soluble metal salt and urea is 1:2, and the volume of deionized water is 30-35 mL.

[0016] Preferably, the magnetic stirring time of step S2 is 30 min, the magnetic stirring rate is 500 r / min, the hydrothermal temperature is 110° C., the hydrothermal time is 10 h, the drying temperature of the hydrothermal product is 60° C., and the drying time of the hydrothermal product is 12 h.

[0017] Preferably, the inert atmosphere in step S3 includes gases such as argon and nitrogen, and the heating rate during the heat treatment is 2-5°C / min, the insulation temperature is 700-900°C, and the insulation time is 1h.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The invention adopts a hydrothermal method and a high-temperature heat treatment process to prepare lightweight, high-performance cobalt-nickel metal particles and a waste tissue-derived carbon composite absorbing material. The preparation process uses waste tissue fibers as a substrate, grows needle-shaped cobalt-nickel composite basic carbonates on the surface of the waste tissue fibers through a hydrothermal process, and then reduces the needle-shaped structures to cobalt-nickel metal particles through a high-temperature heat treatment and embeds them on the surface of the carbon fibers. The lateral dimensions of the tissue-derived carbon fibers are 5-6 μm, and the average particle size of the magnetic metal particles is about 0.47 μm. Thanks to the coupling of electromagnetic components, the composite material achieves good impedance matching. A large number of defects in the carbon structure and the heterogeneous interface between the metal and the carbon induce defect polarization and interface polarization. There are also magnetic coupling and resonance phenomena between the magnetic particles. The synergistic effect of multiple loss mechanisms enables the synthesized cobalt-nickel metal particles and the waste tissue-derived carbon composite absorbing material to have excellent electromagnetic wave absorption performance.

[0020] The advantages of the cobalt-nickel metal particles and waste facial tissue-derived carbon composite absorbing material prepared by the method of the present invention are:

[0021] 1) It realizes the recycling and reuse of waste fabrics, converts waste into valuable absorbing materials, saves the use of original resources, and complies with the principle of sustainable development.

[0022] 2) Using cheap or free waste fabrics as raw materials greatly reduces the cost compared to materials such as carbon fiber and graphene.

[0023] 3) The cobalt-nickel metal particles and waste tissue-derived carbon composite absorber prepared by this method is conducive to multiple reflections of incident electromagnetic waves due to cross-linking between porous carbon fibers.

[0024] 4) The absorbing material prepared by the method of the present invention has good repeatability and component adjustability. Based on the electromagnetic coupling strategy, good impedance matching and multiple loss mechanisms can be obtained.

[0025] 5) When the matching thickness of the prepared absorbing material is 1.3 mm, the maximum reflection loss reaches -40.22 dB and the effective absorption bandwidth is 4.5 GHz. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a SEM image of the cobalt-nickel metal particles synthesized in Example 1 and the carbon composite material derived from waste facial tissue;

[0027] Figure 2 The XRD test results of the cobalt-nickel metal particles and the carbon composite material derived from waste facial tissue paper synthesized in Examples 1-3;

[0028] Figure 3 is the Raman test result of the cobalt-nickel metal particles synthesized in Examples 1-3 and the carbon composite material derived from waste facial tissue;

[0029] Figure 4 is a graph showing the microwave absorption performance of the cobalt-nickel metal particles synthesized in Example 1 and the carbon composite material derived from waste facial tissue;

[0030] Figure 5 is a graph showing the microwave absorption performance of the cobalt-nickel metal particles synthesized in Example 2 and the carbon composite material derived from waste facial tissue;

[0031] Figure 6 This is a graph showing the wave absorption performance of the cobalt-nickel metal particles synthesized in Example 3 and the carbon composite material derived from waste facial tissue. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A composite wave absorbing material of magnetic metal particles and waste fabric-derived carbon is prepared by the following steps:

[0035] (1) Soak the used cotton facial tissue in anhydrous ethanol, filter and wash it, put it into a forced air drying oven, dry it at 60°C, and cut it into 10*10cm2 sheets for later use.

[0036] (2) 1 mmol nickel nitrate, 2 mmol cobalt nitrate and 6 mmol urea were dissolved in 30 mL deionized water and magnetically stirred for 30 min to obtain a uniform solution. The obtained solution was poured into a 50 mL polytetrafluoroethylene liner and a 10*10 cm2 facial tissue was placed therein for hydrothermal treatment. The temperature was set to 110°C and the hydrothermal time was 10 h. After the hydrothermal treatment was completed, the solution was filtered, washed and dried to obtain a composite precursor of basic carbonate and waste facial tissue.

[0037] (3) The basic carbonate and waste facial tissue composite precursor prepared in step (2) are placed in a porcelain boat, placed in a tubular furnace, and heated to 800° C. at a rate of 5° C. / min under an argon atmosphere. The temperature is kept at this temperature for 2 h. After the tubular furnace is cooled to room temperature, cobalt-nickel metal particles and waste facial tissue-derived carbon composite materials are obtained.

[0038] Figure 1 This is a SEM image of the cobalt-nickel metal particles and waste tissue-derived carbon composite material synthesized by the method of the present invention. The prepared composite material consists of micron-sized carbon fibers and metal particles embedded on the surface. The lateral size of the tissue-derived carbon fibers is about 5-6 μm, and the average particle size of the magnetic metal particles is about 0.47 μm. Figure 2 This is the XRD spectrum of the cobalt-nickel metal particles and the carbon composite material derived from waste facial tissue. Compared with the standard card, the obtained product is cobalt and nickel metal. Due to the very small amount of carbon added, no diffraction peak is shown, and there are no other impurities. Figure 3 The Raman spectrum characterization results of the cobalt-nickel metal particles@waste tissue paper derived carbon composite material. D / I G The change in the value indicates that under the experimental conditions of this scheme, the introduction of metal particles and the increase in heat treatment temperature will cause an increase in defects in the carbon structure.

[0039] The coaxial rings were made from the cobalt-nickel metal particles obtained in Example 1 and the carbon composite material derived from waste facial tissue paper in the following manner:

[0040] Cobalt-nickel metal particles @ waste facial tissue derived carbon composite material and paraffin were weighed in a mass ratio of 3:7, ground, heated for 2-3 minutes, and the paraffin was completely melted. The cobalt-nickel metal particles @ waste facial tissue derived carbon composite material and paraffin were gently stirred to evenly mix them, transferred to a mold, and pressure was applied to obtain a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3.04 mm.

[0041] The coaxial ring prepared in Example 1 was tested using a vector network analyzer (3656D), and the reflection loss data after data processing was plotted into a two-dimensional mapping diagram and displayed on Figure 4 The cobalt-nickel metal particles and waste tissue-derived carbon composite absorbing material of the present invention have the best absorbing performance when the heat treatment temperature is 800°C: when the matching thickness is 1.3mm, the maximum reflection loss is -40.22dB, and the effective absorption bandwidth is 4.5GHz (13.5-18GHz).

[0042] Example 2

[0043] (1) Soak the used cotton facial tissue in anhydrous ethanol, filter and wash it, put it into a forced air drying oven, dry it at 60°C, and cut it into 10*10cm2 sheets for later use.

[0044] (2) 1 mmol nickel nitrate, 2 mmol cobalt nitrate and 6 mmol urea were dissolved in 30 mL deionized water and magnetically stirred for 30 min to obtain a uniform solution. The obtained solution was poured into a 50 mL polytetrafluoroethylene liner and a 10*10 cm2 facial tissue was placed therein for hydrothermal treatment. The temperature was set to 110°C and the hydrothermal time was 10 h. After the hydrothermal treatment was completed, the solution was filtered, washed and dried to obtain a composite precursor of basic carbonate and waste facial tissue.

[0045] (3) The basic carbonate prepared in step (2) and the composite precursor of waste facial tissue are placed in a porcelain boat, placed in a tube furnace, and heated to 700° C. at a rate of 5° C. / min under an argon atmosphere, and kept warm for 2 hours. After the tube furnace is cooled to room temperature, cobalt-nickel metal particles and waste facial tissue-derived carbon composite materials are obtained.

[0046] The coaxial rings were made from the cobalt-nickel metal particles obtained in Example 2 and the carbon composite material derived from waste facial tissue paper in the following manner:

[0047] Cobalt-nickel metal particles, waste facial tissue-derived carbon composite material and paraffin were weighed in a mass ratio of 3:7, respectively, and after grinding, they were heated for 2-3 minutes. When the paraffin was completely melted, the cobalt-nickel metal particles, the waste facial tissue-derived carbon composite material and the paraffin were gently stirred to evenly mix them, and then transferred to a mold and pressure was applied to obtain a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3.04 mm.

[0048] The coaxial ring prepared in Example 2 was tested using a vector network analyzer (3656D), and the reflection loss data after data processing was plotted into a two-dimensional mapping diagram and displayed on Figure 5 .

[0049] Example 3

[0050] (1) Soak the used cotton facial tissue in anhydrous ethanol, filter and wash it, put it into a forced air drying oven, dry it at 60°C, and cut it into 10*10cm2 sheets for later use.

[0051] (2) 1 mmol nickel nitrate, 2 mmol cobalt nitrate and 6 mmol urea were dissolved in 30 mL deionized water and magnetically stirred for 30 min to obtain a uniform solution. The obtained solution was poured into a 50 mL polytetrafluoroethylene liner and a 10*10 cm2 facial tissue was placed therein for hydrothermal treatment. The temperature was set to 110°C and the hydrothermal time was 10 h. After the hydrothermal treatment was completed, the solution was filtered, washed and dried to obtain a composite precursor of basic carbonate and waste facial tissue.

[0052] (3) The basic carbonate and waste facial tissue composite precursor prepared in step (2) are placed in a porcelain boat, placed in a tubular furnace, and heated to 900° C. at a rate of 5° C. / min under an argon atmosphere. The temperature is kept at this temperature for 2 h. After the tubular furnace is cooled to room temperature, cobalt-nickel metal particles and waste facial tissue-derived carbon composite materials are obtained.

[0053] The coaxial rings were made from the cobalt-nickel metal particles obtained in Example 3 and the carbon composite material derived from waste facial tissue paper in the following manner:

[0054] Cobalt-nickel metal particles, waste facial tissue-derived carbon composite material and paraffin were weighed in a mass ratio of 3:7, respectively, and after grinding, they were heated for 2-3 minutes. When the paraffin was completely melted, the cobalt-nickel metal particles, the waste facial tissue-derived carbon composite material and the paraffin were gently stirred to evenly mix them, and then transferred to a mold and pressure was applied to obtain a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3.04 mm.

[0055] The coaxial ring prepared in Example 3 was tested using a vector network analyzer (3656D), and the reflection loss data after data processing was plotted into a two-dimensional mapping diagram and displayed on Figure 6 .

[0056] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite wave absorbing material of magnetic metal particles and waste fabric-derived carbon, characterized in that: The material consists of micron-sized carbon fibers and magnetic metal particles embedded on the surface of the micron-sized carbon fibers, and the material is applied to the field of wave-absorbing materials. When the matching thickness is 1.3 mm, the minimum reflection loss reaches -40.22 dB, and the effective absorption bandwidth is 4.5 GHz.

2. The magnetic metal particles and waste fabric derived carbon composite absorbing material according to claim 1, characterized in that: The micron-sized carbon fiber is tissue-derived carbon fiber, and has a lateral size of 5-6 μm.

3. The composite absorbing material of magnetic metal particles and waste fabric-derived carbon according to claim 2, characterized in that: The average particle size of the magnetic metal particles is about 0.47 μm.

4. The method for preparing a composite microwave absorbing material of magnetic metal particles and waste fabric-derived carbon according to any one of claims 1 to 3, characterized in that: The following steps are included: Step S1, soaking the waste fabric in anhydrous ethanol, filtering and washing, drying, and cutting into sheets of 10*10 cm2 for standby use. Step S2, dissolving the soluble metal salt and urea in deionized water, performing magnetic stirring, controlling the stirring time, obtaining a uniform solution, pouring the obtained solution into a polytetrafluoroethylene liner, placing the treated sheet-like waste fabric therein, performing hydrothermal treatment, controlling the hydrothermal time and temperature, filtering, washing and drying after the hydrothermal treatment, and obtaining a composite precursor of basic carbonate and waste fabric; Step S3, heat-treating the basic carbonate and waste fabric composite precursor obtained in step S2 under an inert atmosphere to obtain magnetic metal particles and waste fabric-derived carbon composite materials.

5. The method for preparing a composite wave absorbing material of magnetic metal particles and waste fabric-derived carbon according to claim 4, characterized in that: The waste fabrics in step S1 include daily-use cotton facial tissues and other waste cotton products.

6. The method for preparing a composite wave absorbing material of magnetic metal particles and waste fabric-derived carbon according to claim 5, characterized in that: The soluble metal salt in step S2 is one or more combinations of other acid metal salts such as cobalt nitrate, nickel nitrate, cobalt chloride, nickel acetate, and ferric nitrate, and the ratio between the soluble metal salt and urea is 1:2, and the volume of deionized water is 30-35 mL.

7. The method for preparing a composite wave absorbing material of magnetic metal particles and waste fabric-derived carbon according to claim 6, characterized in that: The magnetic stirring time of step S2 is 30 minutes, the magnetic stirring rate is 500 r / min, the hydrothermal temperature is 110° C., the hydrothermal time is 10 hours, the drying temperature of the hydrothermal product is 60° C., and the drying time of the hydrothermal product is 12 hours.

8. The method for preparing a composite microwave absorbing material of magnetic metal particles and waste fabric-derived carbon according to claim 7, characterized in that: The inert atmosphere of step S3 includes gases such as argon and nitrogen, and the heating rate during the heat treatment is 2-5°C / min, the insulation temperature is 700-900°C, and the insulation time is 1-4h.